2011
DOI: 10.1097/wnf.0b013e318223421f
|View full text |Cite
|
Sign up to set email alerts
|

Is Circadian Rhythm Disruption Important in Obsessive-Compulsive Disorder (OCD)? A Case of Successful Augmentation With Agomelatine for the Treatment of OCD

Abstract: The main augmentation strategy in the treatment of obsessive-compulsive disorder (OCD) is the addition of low-dose dopamine antagonists, such as risperidone. However, the development of additional pharmacological therapeutics is necessary because some patients remain refractory to these strategies. In the present report, we describe an adult male patient with clomipramine treatment-resistant OCD who did not respond to augmentation with risperidone and aripiprazole but who showed clinical improvement with agome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…Furthermore, Monteleone et al [18] reported, in OCD patients, an hyperactivity of the hypothalamic-pituitary-adrenal axis, with an increased secretion of adrenocorticotropic hormone and cortisol and a reduced secretion of melatonin. On the basis of such observations, it is also possible to hypothesize that the restoration of circadian rhythms, such as the improvement of sleep efficiency together with the disappearance of intrasleep awakening, through MT1 and MT2 agonism due to agomelatine augmentation, may have contributed to improve symptomatology confirming the observation of da Rocha and Correa [10]. …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, Monteleone et al [18] reported, in OCD patients, an hyperactivity of the hypothalamic-pituitary-adrenal axis, with an increased secretion of adrenocorticotropic hormone and cortisol and a reduced secretion of melatonin. On the basis of such observations, it is also possible to hypothesize that the restoration of circadian rhythms, such as the improvement of sleep efficiency together with the disappearance of intrasleep awakening, through MT1 and MT2 agonism due to agomelatine augmentation, may have contributed to improve symptomatology confirming the observation of da Rocha and Correa [10]. …”
Section: Discussionsupporting
confidence: 55%
“…It has been reported that agomelatine may be beneficial in the treatment of OCD, although data are limited mainly to case series [8, 9], with initial observations of some efficacy in treatment resistance [10]. …”
Section: Introductionmentioning
confidence: 99%
“…108 When added to classical pharmacological agents used for OCD (eg, escitalopram, venlafaxine, clomipramine, risperidone, and/or aripiprazole), agomelatine has been found to improve OC symptoms in several cases of treatment-resistant OCD. [109][110][111] In some cases, this led to full remission after ∼3 months of treatment, 109 and in reports with longitudinal monitoring, clinical improvements were often sustained over several months. 110,111 A multiple case study reported considerable clinical improvements in three out of six cases of treatment-resistant OCD.…”
Section: Melatonin Agentsmentioning
confidence: 99%
“…[109][110][111] In some cases, this led to full remission after ∼3 months of treatment, 109 and in reports with longitudinal monitoring, clinical improvements were often sustained over several months. 110,111 A multiple case study reported considerable clinical improvements in three out of six cases of treatment-resistant OCD. 112 Interestingly, two of the three individuals who responded to agomelatine initially presented with sleep disruptions.…”
Section: Melatonin Agentsmentioning
confidence: 99%
“…Moreover, in the literature there is a case report of social anxiety disorder effectively treated with agomelatine monotherapy 114 and some reports of agomelatine efficacy in obsessive compulsive disorder both in monotherapy 115,116 and in augmentation. 117 However, well performed studies on these disorders are still lacking.…”
mentioning
confidence: 99%